Species delimitation, genetic diversity and population historical dynamics of Cycas diannanensis (Cycadaceae) occurring sympatrically in the Red River region of China - Jian, Liu; Wei, Zhou; Xun, Gong (Frontiers in Plant Science, 2015)
Delimitating species boundaries could be of critical importance when evaluating the species’ evolving process and providing guidelines for conservation genetics. Here, species delimitation was carried out on three endemic and endangered Cycas species with resembling morphology and overlapped distribution range along the Red River (Yuanjiang) in China: Cycas diananensis Z. T. Guan et G. D. Tao, Cycas parvula S. L. Yang and Cycas multiovula D. Y. Wang. A total of 137 individuals from 15 populations were genotyped by using three chloroplastic (psbA-trnH, atpI-atpH and trnL-rps4) and two single copy nuclear (RPB1 and SmHP) DNA sequences. Basing on the carefully morphological comparison and cladistic haplotype aggregation (CHA) analysis, we propose all the populations as one species, with the rest two incorporated into C. diannanensis. Genetic diversity and structure analysis of the conflated C. diannanensis revealed this species possessed a relative lower genetic diversity than estimates of other Cycas species. The higher genetic diversity among populations and relative lower genetic diversity within populations, as well as obvious genetic differentiation among populations inferred from chloroplastic DNA (cpDNA) suggested a recent genetic loss within this protected species. Additionally, a clear genetic structure of C. diannanensis corresponding with geography was detected based on cpDNA, dividing its population ranges into “Yuanjiang-Nanhun” basin and “Ejia-Jiepai” basin groups. Demographical history analyses based on combined cpDNA and one nuclear DNA (nDNA) SmHP both showed the population size of C. diannanensis began to decrease in Quaternary glaciation with no subsequent expansion, while another nDNA RPB1 revealed a more recent sudden expansion after long-term population size contraction, suggesting its probable bottleneck events in history. Our findings offer grounded views for clarifying species boundaries of C. diannanensis when determining the conservation objectives. For operational guidelines, the downstream populations which occupy high and peculiar haplotypes should be given prior in-situ conservation. In addition, ex-situ conservation and reintroduction measures for decades of generations are supplemented for improving the population size and genetic diversity of the endemic and endangered species.